Tolerance of citrus plants to the combination of high temperatures and drought is associated to the increase in transpiration modulated by a reduction in abscisic acid levels - Zandalinas, Sara I. (BMC Plant Biol, 2016)
BACKGROUND: In natural environments, several adverse environmental conditions occur simultaneously constituting a unique stress factor. In this work, physiological parameters and the hormonal regulation of Carrizo citrange and Cleopatra mandarin, two citrus genotypes, in response to the combined action of high temperatures and water deprivation were studied. The objective was to characterize particular responses to the stress combination. RESULTS: Experiments indicated that Carrizo citrange is more tolerant to the stress combination than Cleopatra mandarin. Furthermore, an experimental design spanning 24 h stress duration, heat stress applied alone induced higher stomatal conductance and transpiration in both genotypes whereas combined water deprivation partially counteracted this response. Comparing both genotypes, Carrizo citrange showed higher phostosystem-II efficiency and lower oxidative damage than Cleopatra mandarin. Hormonal profiling in leaves revealed that salicylic acid (SA) accumulated in response to individual stresses but to a higher extent in samples subjected to the combination of heat and drought (showing an additive response). SA accumulation correlated with the up-regulation of pathogenesis-related gene 2 (CsPR2), as a downstream response. On the contrary, abscisic acid (ABA) accumulation was higher in water-stressed plants followed by that observed in plants under stress combination. ABA signaling in these plants was confirmed by the expression of responsive to ABA-related gene 18 (CsRAB18). Modulation of ABA levels was likely carried out by the induction of 9-neoxanthin cis-epoxicarotenoid dioxygenase (CsNCED) and ABA 8’-hydroxylase (CsCYP707A) while conversion to ABA-glycosyl ester (ABAGE) was a less prominent process despite the strong induction of ABA O-glycosyl transferase (CsAOG). CONCLUSIONS: Cleopatra mandarin is more susceptible to the combination of high temperatures and water deprivation than Carrizo citrange. This is likely a result of a higher transpiration rate in Carrizo that could allow a more efficient cooling of leaf surface ensuring optimal CO(2) intake. Hence, SA induction in Cleopatra was not sufficient to protect PSII from photoinhibition, resulting in higher malondialdehyde (MDA) build-up. Inhibition of ABA accumulation during heat stress and combined stresses was achieved primarily through the up-regulation of CsCYP707A leading to phaseic acid (PA) and dehydrophaseic acid (DPA) production. To sum up, data indicate that specific physiological responses to the combination of heat and drought exist in citrus. In addition, these responses are differently modulated depending on the particular stress tolerance of citrus genotypes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-016-0791-7) contains supplementary material, which is available to authorized users.